A STUDY OF JOURNAL AS ASSESSMENT TOOL IN TEACHING READING INFORMATION REPORT TEXT FOR ELEVENTH GRADERS OF SMA MUHAMMADIYAH 1 PONOROGO - FITRI LAILI KUN MUZAYY, BRILIAN (RETAIN : Journal of Research in English Language Teaching, 2015)
Abstrak Membacamerupakanhal yang pentingdalambelajarbahasainggris (Heinle Brown, 1994:307). Siswamenjadikurangtertarikuntukmembacakarenapengajaran yang kurangbervariatif di kelas (Nuttal in Sadhegi, 2007:195). BerdasarkanKurikulum 2013, untukmenyelesaikanpermasalahantersebutguru kelassebelasdari SMA Muhammadiyah 1 Ponorogomenggunakanjurnalsebagaialatpenilaiandirisendiridalampengajaranteksinformasi report.Sehubungandenganituakanterdapatduapermasalahandalampenelitianini. 1) BagaimanapenggunaanjurnalsebagaialatpenilaiandirisendiriditerapkandikelassebelasSMA Muhammadiyah 1 Ponorogo? dan 2) BagaimanaresponsiswaterhadappenggunaanjurnalsebagaialatpenilaiandirisendiriuntukkelassebelasSMA Muhammadiyah 1 Ponorogo?.Selanjutnyahasilpenelitianakandilaporkandalambentukdeskripsi. Ituberartipenelitianinimenggunakanmetode descriptive qualitative. Selanjutnya instrument penelitian yang digunakanadalahobservasilapangandan interview. Penelitianinidilakukanduahari di SMA Muhammadiyah 1 Ponorogo.Hasilpenelitianmenunjukkanbahwapenggunaanjurnaldikelasberjalandenganbaik, guru mengetahuiperannyadenganbaikdengantidakmendominasipembelajarandikelasdanmembiarkansiswaberkreasidenganidenya. Hal tersebutbisadilihatdarijurnal yang dibuatsiswayagsudahsesuaidenganpendapatahli. Siswajugamenunjukkanrspon yang bagusterhadappenggunaanjurnaldantidakmenemukankesulitandalampenggunaannya. Kesimpulannya, penggunaanjurnalsebagaialatpenilaiandirisendiridalampngajaranmembacateksinformasi report untukkelassebelas di SMA Muhammadiyah 1 Ponorogotelahberhasil. Kata Kunci:AlatPenilaianDiriSendiri, Jurnal, Membaca, TeksInformasi Report Abstract Reading is one of the most important parts in learning English (Heinle Brown, 1994:307). Students become unmotivated to learn reading because the teaching and learning reading in many classrooms is presented in a monotonous strategy (Nuttal in Sadhegi, 2007:195). In order to solve the problem and based on Curriculum 2013, teacher of eleventh graders in SMA Muhammadiyah 1 Ponorogo implements journal as self assessment tool in teaching reading information report text. Finally students will be more motivated on how and what should they do to solve their learning problem in the class. Dealing with this, there will be two research questions will be analyzed in this study. 1) How is the implementation of Journal as self assessment tool in teaching Reading Information report for eleventh graders of SMA Muhammadiyah 1 Ponorogo? and 2) How is the responds of the students towards the using of Journal as self assessment tool in teaching Reading Information report for eleventh graders of SMA Muhammadiyah 1 Ponorogo?. Next the information gathered will be processed in the form of word description. It means this study use descriptive qualitative research. Moreover the data collected through field note and interview. This study finished by two time observations in SMA Muhammadiyah 1 Ponorogo.The result of the study revealed that both teacher and students already have a good understanding about journal implementation, so teacher knows his role well by not dominated the class and let the students explore their ideas. It can be seen from their journal as self assessment tool which already suitable with the expert. The students also show a good response toward the using of journal as self assessment tool and find no difficulties in it. In short, the using of journal as self assessment tool in teaching reading information report text for eleventh graders of SMA Muhammadiyah 1 Ponorogo has already success. Keywords:Self Assessment Tool, Journal, Reading, Information Report Text